Chinese politics and foreign policy under Xi Jinping : the future political trajectory - Ding, Arthur S.; Panda, Jagannath P. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book focuses on China's future under Xi Jinping's authoritarian leadership by examining various facets of the political, economic, social and foreign policy trajectories of contemporary China. It assesses Xi Jinping's power dynamic as the core' leader of the Communist Party of China (CPC) and analyses the impact of Xi's signature domestic policies which demonstrate his political authority within the domestic sphere. Moreover, the book presents Xi's pro-active, assertive and action-oriented outlook as a foundation for China's diplomacy in the new era'. Bringing together an international set of experts in the field who explore critical facets of China under Xi Jinping that deeply influence the regional as well as the global order, the book investigates the impact of Chinese initiatives such as the grand Belt and Road Initiative (BRI), the Asian Infrastructure Investment Bank (AIIB) and the BRICS New Development Bank (NDB). Importantly, the book illustrates US-China relations and outlines how this relationship will intensify in the post-COVID-19 era, which is poised to be one of the biggest challenges and turning points of the Asian Century'. Offering a timely insight into China's future and the trajectory of Xi Jinping's consolidation of power, this book will be of interest to academics in the fields of China Studies, Asian and International Politics and International Relations.
Introduction: Xi Jinping, the 'Peking Order' and China's Post-COVID-19 Political Trajectory: A Primer / Jagannath P. Panda and Arthur S. Ding -- Part I: Xi Jinping and Communist Party of China in Retrospection -- Chapter 1. Xi Jinping Restores the Ideological Imperative so as to Boost His Own Power / Willy Lam -- Chapter 2. Xi Jinping's Reform and Rejuvenation of the United Front Work Department / Drew Thompson -- Chapter 3. Social Governance in China under Xi Jinping: Big Brother Is Watching You! / Jean-Pierre Cabestan -- Chapter 4. The Difficulty of Being Xi Jinping / Avinash Godbole -- Part II: Xi Jinping's Social Governance and China's Commercial Party-State Affairs -- Chapter 5. State-Business Relations under Xi Jinping: Steering the Private Sector and Private Entrepreneurs / Gunter Schubert and Thomas Heberer -- Chapter 6. The Evolution of China's Industrial Policy and 'Made in China 2025' / Tomoo Marukawa -- Chapter 7. Xi Jinping's 'China Dream' and the Future Graph of Chinese Economy / Sriparna Pathak -- Chapter 8. Xi Jinping's Financial Gamble: Will It Succeed? / Priyanka Pandit -- Part III: Xi Jinping and China's Security and Foreign Policy Posturing -- Chapter 9. China's Foreign Policy under Xi -- Reappraisal of China's Partnership Diplomacy / Meng-Chun Liu, Po-Kuan Wu and Chia-Hsuan Wu -- Chapter 10. Xi Jinping, the US-China Rivalry and Beijing's Post- COVID Manoeuvres / Jagannath P. Panda and Eerishika Pankaj -- Chapter 11. China-Southeast Asia Relations in the Era of Xi Jinping / Ian Storey -- Chapter 12. Xi Jinping's 'Asia for Asians', Major Power Diplomacy and India / Atmaja Gohain Baruah -- Chapter 13. Xi Jinping's PLA and China's Regional Security Ambitions / Mrittika Guha Sarkar.
OCLC-licensed vendor bibliographic record.
Keywords: China -- Foreign relations -- 21st century; Xi, Jinping; China -- Politics and government -- 2002-; SOCIAL SCIENCE / Ethnic Studies / General